REKONSTRUKSI PARADIGMA ANALISIS EKONOMI PEMBANGUNAN HUKUM BAGI USAHA MIKRO DALAM RANGKA PENINGKATAN PEREKONOMIAN NASIONAL MENUJU INDONESIA EMAS: Rekonstruksi Paradigma Analisis Ekonomi Pembangunan Hukum Bagi Umkm Dalam Rangka Peningkatan Perekonomian Menuju Indonesia Emas - Lukman, Lukmanul Hakim; Ritonga , Rifandy; Kaplele, Farida (LITIGASI, 2025)
Several regulations related to Micro, Small, and Medium Enterprises (MSMEs) have brought about significant changes in accelerating business growth. The greatest impact has been felt, particularly by micro-enterprises, which were previously considered a less influential sector, but have now proven to contribute significantly to strengthening the real sector. Regulatory changes have also created a new paradigm for micro-enterprises. This is evident in the change in capital requirements, from Rp 50 million to Rp 1 billion. This change reflects a shift in perspective, emphasizing that micro-enterprises are no longer merely informal sectors but can develop into reliable, leading businesses. This phenomenon has become even more evident since the Covid-19 pandemic, when the micro-enterprise sector has proven to be a key pillar of national economic recovery. This development confirms the resilience and strategic role of micro-enterprises in maintaining economic stability. Therefore, reconstructing the legal development paradigm is crucial. This paradigm serves not only as a regulatory instrument but also as a fundamental foundation that shapes the perspectives, mindsets, and actions of micro-entrepreneurs. With supportive and progressive legal support, micro-enterprises are expected to rise to the top, become leading businesses, and make a significant contribution to realizing the vision of Golden Indonesia 2045.